SAUDI VISION 2030 SEBAGAI KATALISATOR SUSTAINABLE DEVELOPMENT GOALS BUTIR KELIMA (KESETARAAN GENDER) DI ARAB SAUDI TAHUN 2015-2022 - Novia Tri Ramadhani; Mhd. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Saudi Arabia is one of the world's largest oil producers. Revenue from the oil sector contributes up to 80% of state revenue. Income dependence on the oil sector creates an unstable situation in the country's economy so that the government seeks to diversify the economy through Saudi Vision 2030. The government is committed to empowering all Saudi Arabian society to the fullest, including women. Through this policy, the government conducted various policies that eliminated various forms of legal discrimination for women in Saudi Arabia. The empowerment of women contained in the Saudi Vision 2030 is in line with the global goals to be achieved in point five of the Sustainable Development Goals related to achieving gender equality. To provide more specific accuracy to the results, the author uses the theory of Gender and Development which is the basic reference in seeing the acceleration of women's empowerment and gender equality in Saudi Arabia. The results of the discussion are obtained by analyzing books, journals, news reports, as well as data listed on various related official pages. The results of the study show that the Saudi Vision 2023 policy plays a role in accelerating gender equality which has a positive impact on the economy and society of Saudi Arabia. This is indicated by the expansion of space for movement and the addition of the work sector for women, followed by a reduction in the female unemployment rate and an increase in economic growth. Keywords: Saudi Vision 2030, Economic Diversification, Gender Equality, Sustainable Development Goals.